Pengembangan Media Pembelajaran Berbasis GeoGebra untuk Meningkatkan Pemahaman Konsep Geometri Transformasi di Kelas XI SMA Negeri 5 Surabaya - Aulia Rahma Fitri; Budi Santoso; Citra Dewi Kusuma (Journal of Science and Mathematics Education, 2026)
This study aims to develop GeoGebra-based learning media for transformation geometry material in class XI Senior High School (SMA) to improve students’ conceptual understanding. The research employed the Research and Development (R&D) approach with the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). Data were collected through validation questionnaires, pre-test, post-test, and student response questionnaires involving 30 students of class XI MIPA 2 at SMA Negeri 5 Surabaya. Validation results from material experts and media experts showed average scores of 4.83 and 4.72 respectively, both categorized as very good. The N-Gain score obtained was 0.58, indicating moderate improvement in students’ conceptual understanding after using the GeoGebra-based media. Furthermore, 83.33% of students achieved the minimum completion criteria compared to only 23.33% before the intervention. Students’ positive responses reached 89.7%, indicating high acceptance and engagement with the developed media. These findings demonstrate that GeoGebra-based learning media is effective and feasible for use in transformation geometry learning.